جدلية الدّرس البلاغي والإعجاز القرآني (من خلال جهود العلماء القدامى) - القايدي محمد (University of Eloued جامعة الوادي, 2023)
ملخص: مثّل القرآن الكريم معجزة الإسلام الخالدة التي تحدت الثقلين على الإتيان بمثله، ولمّا كانت هذه المعجزة من جنس ما برع فيه قوم النبي محمد صلى الله عليه وسلم -الذين تفننوا في نظم الشعر-فقد اعتبر الإعجاز اللّغوي – البلاغي من أبرز أوجه الإعجاز فيه. ومثل نزول القرآن الكريم لحظة فارقة في تاريخ العربي واللغة العربية التي ارتقى بها إلى مصاف اللّغات العالمية بعد أن كانت لغة تائهة في الصحراء بين قبائل العرب. وتأتي هذه الدراسة للبحث في العلاقة الجدلية بين القرآن الكريم وعلم البلاغة من ناحيتين: ناحية أولى في مستوى تأثير الإعجاز البلاغي للقرآن الكريم في نشأة الدرس البلاغي في التاريخ العربي. وناحية ثانية تهتم بدور الدراسات البلاغية في فهم النص القرآني وأثرها في نشأة التفاسير البلاغية للقرآن الكريم. وقد اعتمد الباحث في دراسته لتحقيق هذه الأهداف على المنهج التاريخي والتحليلي من خلال سبر غور المصنفات والمؤلفات ذات الصلة بموضوع الدراسة. وفي الخاتمة توصلت الدراسة لمجموعة من النتائج من أبرزها: أهمية الدين الإسلامي والقرآن الكريم تاريخيا في تنشيط وإثراء اللغة العربية وحمايتها من الانقراض فضلا عن جعلها لغة عالمية خالدة. Abstract : The Holy Qur’an represented the eternal miracle of Islam, which challenged the two races to come up with the same, and since this miracle was of the same kind as the people of the Prophet Muhammad, may God’s prayers and peace be upon him, excelled in - who excelled in poetry systems - the linguistic - rhetorical miracle was considered one of the most prominent aspects of its miracle. Like the revelation of the Noble Qur’an, a defining moment in the history of the Arab and the Arabic language, which elevated it to the ranks of the universal languages after it was a lost language in the desert among the Arab tribes. This study comes to investigate the dialectical relationship between the Holy Qur’an and the science of rhetoric from two aspects: the first aspect is the level of the impact of the rhetorical miracle of the Holy Qur’an on the emergence of the rhetorical lesson in Arab history. On the other hand, it is concerned with the role of rhetorical studies in understanding the Qur’anic text and its impact on the emergence of rhetorical interpretations of the Holy Qur’an
Keywords: الإعجاز القرآني؛ البلاغة؛ القرآن الكريم؛ الإعجاز اللّغوي.; Quranic miracles; rhetoric; The Holy Quran; Linguistic miracle.